Boswellic acids ameliorate doxorubicin-induced nephrotoxicity in mice: a focus on antioxidant and antiapoptotic effects. Issue 1 (2nd January 2019) - Sami, Manal M.; Ali, Eman A.I.; Galhom, Rania A.; Youssef, Amal M.; Mohammad, Hala M.F.
ABSTRACT: Doxorubicin (DXR) is a broad-spectrum anti-cancer. Doxorubicin irreversible toxicity resulting from oxidative damage limits its therapeutic use. Boswellic acids (BAs) are inhibitors of 5-lipoxygenase and have been used in traditional medicine for their powerful anti-inflammatory effects and cellular protective effects. This study tested the protecting mechanisms of BAs against nephrotoxicity induced by DXR in mice and explored their antioxidant and antiapoptotic activities in the form of immunohistochemical expression of Bcl2 in the tissue of the kidney. DXR (6 mg/kg) was injected intraperitoneally weekly to mice along with BAs (125, 250 and 500 mg/kg) daily. The experiment continued for three weeks. It was found that the elevated serum urea and creatinine in DXR-treated mice were ameliorated by BAs. Furthermore, BAs decreased malondialdehyde and increased glutathione levels in renal tissues of DXR-treated mice. The immunostained kidney tissue showed an anti-apoptotic effect for BAs as it increased expression of Bcl2 in mice co-treated with BAs with DXR compared to the DXR control mice. Western blot analysis demonstrated that DXR control group showed greater expression for renal caspase 3 and mice administered BAs (125–500 mg/kg) along with DXR showed significant downregulations. These findings were supported by the DNA laddering assay and histopathological examination of renal tissues stained with haematoxylin+eosin or periodic acid Schiff. Results suggest BAs for nephroprotection against toxicity induced by DXR.